Environmental assessment of food waste valorization in producing biogas for various types of energy use based on LCA approach. (April 2016) - Woon, Kok Sin; Lo, Irene M.C.; Chiu, Sam L.H.; Yan, Dickson Y.S.
Highlights: Three scenarios with food waste to various types of energy use are compared via LCA. For damage category, biogas vehicle fuel as petrol substitute is the best scenario. It is also the best scenario when meeting the government's emission reduction targets. The use of biogas vehicle fuel as a petrol substitute reduces GHG in transport sector. Abstract: This paper aims to evaluate the environmental impacts of valorizing food waste for three types of energy use, namely electricity and heat, city gas, and biogas fuel as a petrol, diesel, and liquefied petroleum gas substitute for vehicle use, with reference to the Hong Kong scenario. The life cycle based environmental assessment is conducted from bin-to-cradle system boundary via SimaPro 7.2.4 with ReCiPe 1.04. All of the inventory data of included processes is based on reports of government and industrial sectors. The results show that biogas fuel as a petrol substitute for vehicle use is advantageous over other types of energy use in regard to human health and ecosystems, and it is also the best considering the government's future emission reduction targets set out for the power and transport sectors in Hong Kong. By turning 1080 tonnes per day of food waste into biogas vehicle fuel as petrol substitute, it reduces 1.9% of greenhouse gas emissions in the transport sectors, which results a larger decrease of GHG emissions than the achieved mitigation in Hong Kong from 2005 to 2010.